FACTORS AFFECTING FLORICULTURE FARMERS’ PRODUCTIVITY: A CASE STUDY OF PUNE - et. al., Mridul Khanna (International Journal of Modern Agriculture, 2021)
The floriculture industry in India is identified as a â€˜sunrise industryâ€™ and has been accorded 100% export oriented status by the Indian government. Floriculture has the potential to increase farm incomes and the production of cut flowers in this format was fuelled by the liberalization of trade policies and ease of doing business. The literature on the economic aspects of the Indian floriculture farmers, however, is scant. Based on the structured interviews of 35 purposively selected floriculture enterprises (farmers) from Talegaon’s Floriculture Park in 2018, the paper identifies the factors affecting farm productivity and highlights the employment and marketing channels followed by floriculture farms. This study finds that the benefit-cost ratio is 1.74, which shows that the return on investment is high. On the other hand, farm productivity is 1.13 lakh rose stem per acre, which has a scope to improve. The regression results indicate diminishing marginal returns, when one increases the acreage under rose. Export orientation fetches higher returns compared to domestic markets. This paper expands the discourse on floriculture enterprises’ productivity and returns